2021
DOI: 10.1097/dad.0000000000002075
|View full text |Cite
|
Sign up to set email alerts
|

A Young Boy With Hemophagocytic Lymphohistiocytosis Presenting With Vaccine-Related Granulomatous Dermatitis: A Case Report and Literature Review

Abstract: Cutaneous eruptions associated with hemophagocytic lymphohistiocytosis (HLH) have been reported in 6%-63% of patients. Clinical findings of these skin lesions vary widely and include maculopapular rashes, ulcers, and violaceous nodules. Corresponding histologic findings are also variable and are considered nonspecific. We report the case of a 4-year-old boy who initially developed a widespread popular-pustular rash 2 weeks after his 12month measles, mumps, and rubella vaccinations. These resolved with scarring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, rubella PCR or immunohistochemistry were not reported. 16 UNC13D-associated disease largely appears to be a recessive condition; thus, the single variant in our patient, even if pathogenic, would not be expected to lead to symptoms. However, the literature does suggest that certain heterozygous variants in UNC13D could potentially have an association with an increased risk for immune dysregulation, [17][18][19] thus the variant may still be significant.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, rubella PCR or immunohistochemistry were not reported. 16 UNC13D-associated disease largely appears to be a recessive condition; thus, the single variant in our patient, even if pathogenic, would not be expected to lead to symptoms. However, the literature does suggest that certain heterozygous variants in UNC13D could potentially have an association with an increased risk for immune dysregulation, [17][18][19] thus the variant may still be significant.…”
Section: Discussionmentioning
confidence: 73%
“…Of interest, in one case report, a patient with biallelic mutations of UNC13D developed a widespread papular–pustular eruption following MMR vaccination at the age of 2 years, and skin biopsies showed a necrotizing granulomatous process. However, rubella PCR or immunohistochemistry were not reported 16 . UNC13D‐ associated disease largely appears to be a recessive condition; thus, the single variant in our patient, even if pathogenic, would not be expected to lead to symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Another patient with FHL3 presented with vaccine‐related granulomatous dermatitis in the absence of other symptoms. The infiltration of macrophage into the tissue may potentially induce granuloma formation 29 . It is suggested that a rash may also be the primary symptom of FHL3 onset, and the measles–mumps–rubella vaccine should be avoided in cases of cytotoxic dysfunction 30 …”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of macrophage into the tissue may potentially induce granuloma formation. 29 It is suggested that a rash may also be the primary symptom of FHL3 onset, and the measles-mumps-rubella vaccine should be avoided in cases of cytotoxic dysfunction. 30 The diagnosis of patients with FHL3 is complex.…”
Section: Nk Cytotoxicitymentioning
confidence: 99%
“…HLH can develop with many different immune triggers, including infection and vaccination. 4,5 Reports show HLH in adults can be associated with multiple vaccines, including COVID-19 vaccination. 5 While HLH associated with vaccination is not new, we have yet to understand HLH associated with mRNA-based vaccines in pediatric patients.…”
Section: E T T E R T O T H E E D I T O R Epstein-barr Virus-positive ...mentioning
confidence: 99%